MiR-145 regulates steroidogenesis in mouse primary granulosa cells by targeting Arpc5 and subsequent cytoskeleton remodeling - Lanfang MA; Shuo WANG; Jun YANG; Weicheng TANG; Zhangying WU; Lili CAO; Aiyue LUO; Fangfang FU; Shuhong YANG; Shixuan WANG (The Society for Reproduction and Development, 2023)
MicroRNA (miR)-145 is enriched in the follicular granulosa cells (GCs) of 3-week-old mice. Downregulating miR-145 inhibits the proliferation and differentiation of GCs and induces evident changes in their cytoskeleton. In this study, we examined how miR-145 induces cytoskeletal changes in mouse GCs and its potential mechanism in regulating GC steroidogenesis. We found that actin related protein 2/3 complex subunit 5 (Arpc5) is a target of miR-145. The miR-145 antagomir increased ARPC5 expression but not β-ACTIN, β-TUBULIN, and PAXILLIN expression. Arpc5 overexpression inhibited GC proliferation, differentiation, and progesterone synthesis. Furthermore, the expression of progesterone synthesis-associated enzymes was downregulated in the Arpc5 overexpression group, and the GC cytoskeleton exhibited evident changes. We conclude that Arpc5, a new target of miR-145, regulates primary GC proliferation and progesterone production by regulating the cytoskeleton remodeling.